Pengaruh Komitmen Organisasi, Kepemimpinan dan OCB Terhadap Motivasi Pelayanan Publik Pegawai Kecamatan - Syamsir Syamsir (Faculty of Social Science, Universitas Negeri Padang, 2026)
This article tried to explore the extent to which organizational commitment, leadership and organizational citizenship behavior (OCB) affected the public service motivation (PSM) of subdistrict employees in Limapuluh Kota Regency. The background of this study was the low PSM that has an impact on the quality of public services, especially in several subdistrict areas. The population in this study included all subdistrict employees in Limapuluh Kota Regency, with 94 respondents selected randomly and proportionally. Data were collected through questionnaires and analyzed using multiple linear regression. The finding of this study showed that organizational commitment, leadership, and OCB simultaneously and partially had significant effects on public service motivation. Based on these results, this study recommended strengthening organizational commitment, leadership, public service motivation in employee recruitment, and organizational culture, providing institutional support, and encouraging positive behavior to increase the enthusiasm of the apparatus in public services.